Joint statement on evidence-based practices in mechanical ventilation: suggestions from two Brazilian medical societies - Juliana Carvalho Ferreira; Arthur Oswaldo de Abreu Vianna; Bruno Valle Pinheiro; Israel Silva Maia; Sérgio Vasconcellos Baldisserotto; Alexandre Marini Isola (Jornal Brasileiro de Pneumologia)
ABSTRACT Mechanical ventilation can be a life-saving intervention, but its implementation requires a multidisciplinary approach, with an understanding of its indications and contraindications due to the potential for complications. The management of mechanical ventilation should be part of the curricula during clinical training; however, trainees and practicing professionals frequently report low confidence in managing mechanical ventilation, often seeking additional sources of knowledge. Review articles, consensus statements and clinical practice guidelines have become important sources of guidance in mechanical ventilation, and although clinical practice guidelines offer rigorously developed recommendations, they take a long time to develop and can address only a limited number of clinical questions. The Associação de Medicina Intensiva Brasileira and the Sociedade Brasileira de Pneumologia e Tisiologia sponsored the development of a joint statement addressing all aspects of mechanical ventilation, which was divided into 38 topics. Seventy-five experts from all regions of Brazil worked in pairs to perform scoping reviews, searching for publications on their specific topic of mechanical ventilation in the last 20 years in the highest impact factor journals in the areas of intensive care, pulmonology, and anesthesiology. Each pair produced suggestions and considerations on their topics, which were presented to the entire group in a plenary session for modification when necessary and approval. The result was a comprehensive document encompassing all aspects of mechanical ventilation to provide guidance at the bedside. In this article, we report the methodology used to produce the document and highlight the most important suggestions and considerations of the document, which has been made available to the public in Portuguese.